If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6(a + x) = b + -1a + 4x (a * 6 + x * 6) = b + -1a + 4x (6a + 6x) = b + -1a + 4x Reorder the terms: 6a + 6x = -1a + b + 4x Solving 6a + 6x = -1a + b + 4x Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add 'a' to each side of the equation. 6a + a + 6x = -1a + b + a + 4x Combine like terms: 6a + a = 7a 7a + 6x = -1a + b + a + 4x Reorder the terms: 7a + 6x = -1a + a + b + 4x Combine like terms: -1a + a = 0 7a + 6x = 0 + b + 4x 7a + 6x = b + 4x Add '-6x' to each side of the equation. 7a + 6x + -6x = b + 4x + -6x Combine like terms: 6x + -6x = 0 7a + 0 = b + 4x + -6x 7a = b + 4x + -6x Combine like terms: 4x + -6x = -2x 7a = b + -2x Divide each side by '7'. a = 0.1428571429b + -0.2857142857x Simplifying a = 0.1428571429b + -0.2857142857x
| 12(4x-2)=4(12x+4) | | -7y-14=-4y-5 | | log(x+2)+log(x-1)=log(28) | | 2-8(n-8)=8(3n+5)-5 | | 9X+10=22 | | 8+10s-3=8s+68-5s | | 34=3t+4 | | y^2-5-y=0 | | 5x^2+32=0 | | 23+3y-4=14y-13-3y | | x+24+3x=-16-3x-23 | | -8-5=5x+2-4x | | 3(2n+4)=2(3n+6) | | -4x-4x=23-7 | | -9z-16=-7z | | 0.7(n-15)=1.2(n-9) | | 0.1v-1.1=-1.3v+3.1 | | (2x+7)(3x-5)=0 | | 2-15= | | 9+6(-4x-1)=6(-8x-3)-4 | | 8u-11=2u-5 | | 6(3+y)+4y=13 | | -3x=x-4(2+x) | | -9x+10=-(9x-10) | | 4z+12z=144 | | 3z=12-21 | | ln(x+1)+ln(x-1)=ln(3) | | -6t-10=-2t+2 | | 9w-11=7w+1 | | -5-3(6y+3)=-4(-4y+3)-1 | | -2(7-2x)=4x+8 | | 9x-16x=45-60 |